PENGARUH SUPERVISI KEPALA SEKOLAH DAN BUDAYA KERJA TERHADAP PROFESIONALISME GURU SEKOLAH DASAR NEGERI DI KECAMATAN BARAMBAIKABUPATEN BARITO KUALA - Herianto, Muhammad; Khuzaini, Khuzaini; Muhammad Yuliansyah (Journal of Innovation Research and Knowledge, 2024)
This research is motivated by the fact that there are still state elementary school teachers in Barambai District who have less than ideal performance, from the aspects of learning planning, learning implementation to learning evaluation. This research aims to analyze: 1) the influence of school principal supervision on teacher professionalism, 2) Is there an influence of work culture on teacher professionalism, 3) the influence of academic supervision and work culture together on teacher professionalism. This research is acorrelational descriptive research with path analysis. The research population was state elementary school teachers in Barambai District with a population of 117 people with a sample population of 91. Data was collected through questionnaires and then analyzed descriptively and inferentially using SPSS 25. The results of the research show: 1) There is an influence of principal supervision on the professionalism of elementary school teachers in Barambai sub-district, Barito Kuala Regency, amounting to 10.2%. However, there is still a very low perception of Principal supervision, especially in terms of follow-up programs. Meanwhile, the teacher professionalism variable with the lowest score is indicator Y.9 related to the evaluation of learning outcomes carried out by teachers periodically. 2) There is an influence of work culture on the professionalism of elementary school teachers in Barambai District, Regency by 27%. However, there is still a very low perception of work culture, especially in terms of teachers' attitudes towards informing colleagues when they get new information. Meanwhile, the teacher professionalism variable with the lowest score is indicator Y.9 related to the evaluation of learning outcomes carried out by teachers periodically. 3) There is an influence of the Principal's academic supervision and work culture on the professionalism of elementary school teachers in the Barambai subdistrict, Barito Kuala Regency, amounting to 42.9%. However, there is still a very low perception of teacher professionalism, especially in terms of evaluation of learning outcomes carried out by teachers periodically.